SUN-271 Langerhans Cell Histiocytosis: A Difficult Diagnosis in Cranial Diabetes Insipidus - Ng, Ivy Hoi Yee (J Endocr Soc, 2020)
Background Langerhans cell histiocytosis (LCH) is a myeloid neoplastic disorder that is rare in adults, with a reported incidence of 1-2 cases per million per year. Cranial diabetes insipidus (CDI) is the most common and often the first endocrine manifestation of LCH, when histiocytes infiltrate the pituitary. Anterior pituitary dysfunction, when present, usually develops after onset of CDI. Unlike most other etiologies of CDI, multisystem involvement is frequent in LCH, especially the bones, skin, and lungs. Case A 23-year-old man of good past health presented with 3 months of polyuria and polydipsia in 2015. CDI was confirmed by water deprivation test, and his symptoms resolved with DDAVP treatment. There were no anterior pituitary hormone deficiencies on presentation. Pituitary MRI showed loss of the posterior bright spot and a contrast enhancing pituitary stalk thickening (PST) of 5 mm, with no compression on the optic chiasm. Lumbar puncture showed no evidence of CNS infection or neoplastic cells. Beta HCG, AFP, IgG4, ANA, and chest Xray were unremarkable. Three months later he developed central hypogonadism, and was treated with testosterone after sperm banking. A repeat MRI showed persistent PST of 5 mm, and biopsy of the pituitary suggested lymphocytic infundibulo-hypophysitis (LIH). Unfortunately the biopsy was complicated with irreversible focal visual field defect. It was then noted that a bone scan had been arranged earlier for intermittent left hip pain, which revealed a 3.5 cm osteolytic lesion over the left ilium. The concomitant pituitary and bone lesions thus make LCH the more likely diagnosis. However bone biopsy showed nonspecific fibrosis only. The pathologist was then contacted for further immunohistochemical analysis. This identifies clusters of Langerhans cells with positive stain for S100, CD1a, and Langerin (LCH cell markers) in the pituitary tissue, and BRAF V600E mutation was detected by PCR, compatible with the diagnosis of LCH. Systemic chemotherapy was proposed due to multisystemic disease, but was declined by patient. At 4 years of follow-up, the PST spontaneously regressed to 2 mm but the CDI and central hypogonadism persisted. Conclusion Our case illustrates the diagnostic challenge in a patient presenting with CDI, given a pituitary biopsy with histological features mimicking LIH and an inconclusive bone biopsy. However, a diagnosis of LIH would not explain for the unusual bone lesion in a young man, and bone biopsies can be prone to crush artifacts limiting analysis. The importance of actively looking for and biopsying extracranial lesions before biopsying the pituitary cannot be understated as the latter entails risks of hypopituitarism and visual defect, as had happened to our patient. When clinical and pathologic findings do not match, communication with the pathologist for histological review had been essential in establishing the diagnosis of LCH.